EU Public Procurement Policy - Deaconu, Ştefan; Lupu, Andrei (The Policies of the European Union from a Central European Perspective, 2022)
A single European market cannot rule out the participation of the State, through public procurement, among other private actors on the market. However, specific rules have been imposed regarding the State’s actions, aiming to secure a free market and to prevent protectionism. The 2014 new set of European directives have updated this approach, setting transparency, equal treatment, and open competition as the main objectives of the public procurement procedures. The CEECs, based on their common history regarding centralized economies, require a special approach when it comes to the state’s intervention on the market. Therefore, the current study aims to analyze a series of particularities regarding the transposition of the 2004 and 2014 European directives on public procurement in the CEECs. Also, specific recent essential events with a direct impact regarding public procurement will be examined, such as the COVID-19 pandemic or the implementation of the Recovery and Resilience Facility (RRF). Keywords: public procurement policy, EU public procurement agreements, arbitrability, price adjustment,emergency public procurement